Tribological properties of PEO nanocomposite coatings on titanium formed in electrolyte containing ketoconazole. (October 2016) - Sharifi, Hossein; Aliofkhazraei, M.; Darband, Ghasem Bratai; Rouhaghdam, A. Sabour
Abstract: Nanocomposite coatings were formed on commercial pure titanium through plasma electrolytic oxidation (PEO) process in a phosphate-based electrolyte containing ketoconazole and alumina nanoparticles. The procedure was performed by direct current and current density was kept constant. The effects of concentration of ketoconazole in the electrolyte on growth of coatings, absorption of alumina nanoparticles, morphology, chemical structure and mechanical behavior of coatings were studied by means of Fourier-transform infrared spectroscopy, scanning electron microscopy, nanoindentation and pin-on-disk wear test. Existence of ketoconazole in the electrolyte was observed to increase alumina nanoparticles absorption within coatings and consequently decrease porosity. Mechanical behavior of coating indicated that the rate of hardness to Young׳s modulus was increased and consequently wear resistance of coating was improved. Highlights: Nanocomposite coating is formed using PEO treatment in electrolyte contain ketoconazole. According to FTIR analysis, ketoconazole lead to increase alumina nanoparticle absorption. Effects of ketoconazole on microstructure and mechanical behavior of coatings are studied. By addition of ketoconazole in PEO electrolyte, wear resistance of coating is improved.